SP0002 Novel animal models in systemic sclerosis. (15th June 2017) - Yu, X
Abstract : Systemic sclerosis (SSc) is a severe autoimmune disease with a considerable reduction of life expectancy. Autoimmunity, vasculopathy and fibrosis are three hallmarks of SSc, while the pathogenesis of the disease is largely unknown. Animal models of SSc provide an excellent tool to for exploring the disease pathogenesis of the disease. Aiming to provide a concise and curate updates in the field of animal models of SSc, this lecture will concentrate on emerging novel animal models and highlight new development and their impact on understanding pathogenesis of SSc. Disclosure of Interest: None declared